PENGARUH KECUKUPAN ANGGARAN, KETEPATAN WAKTU INFORMASI AKUNTANSI MANAJEMEN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (Studi Empiris pada RS. Ortopedi Prof. Dr. R. Soeharso Surakarta) - Hj - Nurchayati; Widi - Hariyanti (Serat Acitya, 2015)
This researched was conducted to examine the effect budget adequacy, timelines accountancy management information and organizational commitment on managerial performance, by using the unit analysis is structurally officials who worked at the Ortopedi Prof Dr. R. Soeharso hospital in Surakarta. The sampling technique used is the census method, where the entire population sampled. Population in this research is structurally officials who worked at the Ortopedi Prof Dr. R. Soeharso hospital in Surakarta. Result from data processing, so can be taken conclusion as follows there positive influence and significant between variable budget adequacy, timelines accountancy management information and organizational commitment on managerial performance with significant and a significance value it can be concluded that the model is feasible research, and may explain the significant effect between variables budget adequacy, timelines accountancy management information and organizational commitment are simultaneously on variable managerial performance. Result analysis of the coefficient determination indicates that the variables budget adequacy, timelines accountancy management information and organizational commitment variation affecting the variable managerial performance.